New species of Uropodina from Madagascar (Acari: Mesostigmata) - Kontschán, Jenő; Starý, Josef (Zootaxa, 2014)
Seven new species and one new genus of Uropodina are described from Madagascar. The third Afrotropical species of Polyaspis is described (Polyapis (Polyaspis) madagascarensis sp. nov.), with a key to the Afrotropical species of the genus. The first species of Dinychus from the Afrotropical region is described, as Dinychus lepus sp. nov.. An unusual new species of Trichouropoda species is described as Trichouropoda madagascarica sp. nov.. A new genus (Malagana gen. nov.) is described, with type species Malagana rotunda sp. nov.. The genus Pulchellaobovella is recorded from the Afrotropical Region for the first time, on the basis of Pulchellaobovella madagascarica sp. nov., with nomenclatural notes on the genera Pulchellaobovella and Janetiella. Uroobovella graeca Kontschán, 2010 is moved into the genus Pulchellaobovella, as Pulchellaobovella graeca (Kontschán, 2010b) comb. nov. Two new species of Rotundabaloghia (Circobaloghia) are described, Rotundabaloghia (Circobaloghia) ermilovi sp. nov. and Rotundabaloghia (Circobaloghia) kaydani sp. nov.